Taro Ada Taro Gau Sebagai Indikator Kinerja Auditor Wanita Di Kantor Akuntan Publik Kota Makassar - Tenriwaru Tenriwaru; Yabanila Yabanila; Reza Ramdani (LPPM UBP, 2023)
The purpose of this research is to find out how taro ada taro gau is understood as an indicator of the performance of female auditors and to find out how a female auditor carries out performance using the term taro ada taro gau principle as motivation in completing work. This research was conducted from February to April 2023 at the Makassar City Public Accounting Office. The type of data used in this research is qualitative data. The data sources in this research are primary data obtained directly from interviews and secondary data. The results of this research show that the understanding of the taro ada taro gau philosophy among female auditors at the Makassar Public Accounting Firm is proven to mean that each auditor understands and applies and makes the principles held have an influence on the auditor's performance. This is what can be seen in the attitude of the female auditors at the Makassar Public Accounting Firm in carrying out their duties with good self-control as a form of siri. The values ​​of the Taro Ada Taro Gau philosophy as motivation to complete the work of female auditors are carried out well. The internalization of the values ​​of the Taro Ada Taro Gau philosophy can be seen from the formation of the character of a female auditor who speaks well, is friendly and respects others.